1992
DOI: 10.1111/j.1651-2227.1992.tb12300.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal Y sequences in Smith‐Lemli‐Opitz syndrome with total failure of masculinization

Abstract: We report an infant with characteristics of Smith-Lemli-Opitz syndrome who had anteverted nostrils, apparently low-set ears, micrognathia, high-arched palate, cleft palate, growth and psychomotor retardation, hypotonia, poor suck, cerebral hypotrophy and double renal pelvis and ureter. An EEG showed spike waves in the right temporal area. The patient appeared to have normal internal and external genitalia of the female type. Both ovaries were dysplastic. The karyotype was 46,XY. All of 26 loci on the Y chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The X-ray luminosities and temperatures of the groups appear to be consistent with the well-known correlation in clusters (e.g., Mushotzky 1984, Edge & Stewart 1991, David et al 1993, Mushotzky & Scharf 1997, Fukazawa 1997. In Figure 6 we show the 0.5−10 keV X-ray luminosity L X at 0.5 Mpc against the X-ray temperature kT of our groups (square points) compared to a sample of clusters and groups studied with ASCA by Fukazawa (1997). The groups fall on the lower luminosity end of the relation defined by the clusters.…”
Section: X-ray Luminositiessupporting
confidence: 82%
See 4 more Smart Citations
“…The X-ray luminosities and temperatures of the groups appear to be consistent with the well-known correlation in clusters (e.g., Mushotzky 1984, Edge & Stewart 1991, David et al 1993, Mushotzky & Scharf 1997, Fukazawa 1997. In Figure 6 we show the 0.5−10 keV X-ray luminosity L X at 0.5 Mpc against the X-ray temperature kT of our groups (square points) compared to a sample of clusters and groups studied with ASCA by Fukazawa (1997). The groups fall on the lower luminosity end of the relation defined by the clusters.…”
Section: X-ray Luminositiessupporting
confidence: 82%
“…We assume that the gas is isothermal, since this is consistent with our spatially resolved spectral analysis (Table 2), and take the gas temperatures from the global spectral results in Table 2. Most groups for which the temperature profile has been measured are indeed consistent with being isothermal (e.g., see Mulchaey et al 1996 and references therein, Fukazawa et al 1996), with the exception of those whose central regions may harbor cooling flows (e.g., Fukazawa et al 1996, 1996b, Ponman & Bertram 1993. The total binding masses at 0.5 Mpc for our groups are (3 − 8) × 10 13 M ⊙ (Table 7), higher than those reported for lower temperature groups by Pildis et al (1995) and , but comparable to those reported for six MKW and AWM poor clusters by Kriss et al (1983) using Einstein Observatory data.…”
Section: Masses and Mass Ratiosmentioning
confidence: 75%
See 3 more Smart Citations